Governança em Universidades Federais brasileiras – uma contribuição a partir do IG-SEST - Clêuber Pimentel Barbosa (2019)
The general objective of this study is to validate IG-SEST as a governance mechanism in Brazilian Federal Universities. For this, it was based on the methodology of elaboration of the referred index adapted to the case of the Brazilian Federal Universities, based on the requirements made by the TCU and pertinent norms to the universities maintained by the Union, in order to measure the level of governance following the methodology of this index. This study is important for the public interested in the governance issue, notably the public university auditors and managers, who will be able to analyze how the governance mechanisms can be used so that the university can achieve a better level of governance and thus improve the management, as well as promoting greater transparency. This research can be characterized as exploratory, descriptive and documentary in nature. For this, we used the quantitative research, which examined fifteen universities, chosen by the Webometrics Ranking, and selected three Federal Universities from each geographical region of the country. The documents and websites of these universities were analyzed to build the index proposed in this work. In the qualitative research, a semi-structured interview was applied to the chief auditor of a university chosen in each geographic region of Brazil. The results showed convergence by pointing out that the variables raised present, mostly, evidence of low level of governance in the evaluated universities, which may indicate an insufficient effort to promote better governance practices in these institutions. According to the index proposed in this study, it is possible to verify that only 3 universities were able to reach Level 1 of governance, while the others were able to reach only Level 2, which shows that the universities examined do not make significant efforts to promote governance. . And this shows that, to improve the level of governance, it is necessary to implement good governance practices and promote a training policy for its employees and teachers on the subject.